Gastrodin Suppresses the Amyloid β-Induced Increase of Spontaneous Discharge in the Entorhinal Cortex of Rats - Peng-zhi Chen; Hui-hui Jiang; Bo Wen; Shuan-cheng Ren; Yang Chen; Wei-gang Ji; Bo Hu; Jun Zhang; Fenglian Xu; Zhi-ru Zhu (Neural Plasticity)
Accumulated soluble amyloid beta- (Aβ-) induced aberrant neuronal network activity may directly contribute to cognitive deficits, which are the most outstanding characteristics of Alzheimer’s disease (AD). The entorhinal cortex (EC) is one of the earliest affected brain regions in AD. Impairments of EC neurons are responsible for the cognitive deficits in AD. However, little effort has been made to investigate the effects of soluble Aβ on the discharge properties of EC neurons in vivo. The present study was designed to examine the effects of soluble Aβ1−42 on the discharge properties of EC neurons, using in vivo extracellular single unit recordings. The protective effects of gastrodin (GAS) were also investigated against Aβ1−42-induced alterations in EC neuronal activities. The results showed that the spontaneous discharge of EC neurons was increased by local application of soluble Aβ1−42 and that GAS can effectively reverse Aβ1−42-induced facilitation of spontaneous discharge in a concentration-dependent manner. Moreover, whole-cell patch clamp results indicated that the protective function of GAS on abnormal hyperexcitability may be partially mediated by its inhibitory action on Aβ1−42-elicited inward currents in EC neurons. Our study suggested that GAS may provide neuroprotective effects on Aβ1−42-induced hyperactivity in EC neurons of rats.